Enhanced Thermoelectric Properties Of Skutterudite Thick Film Polyvinyl Alcohol Assisted From The Post-Deposition Annealing Effect - Mohd Sabri, Mohd Faizul; Sabran, Nuur Syahidah; Fadzallah, Iman Aris; Ono, Takahito; Samat, Khairul Fadzli; Yusuf, Siti Nor Farhana; Saidur, Rahman (IOP Publishing Ltd, 2021)
Thick film has demonstrated a high Seebeck coefficient, S, for thermoelectric material but it is very challenging to obtain through cost-effective techniques. Electrodeposition is adopted to tailor the film's thickness, t, facilitated by additive and heat treatment to boost the S. Here, we report the influence of two varied molecular weight (Mw) of polyvinyl alcohol (PVA) as additive and the post-deposition annealing temperature on Skuterrudite (cobalt triantimonide, CoSb3) thick films. The films are synthesized at room temperature via chronoamperometry from an aqueous electrolyte consisting of cobalt and antimony ions assisted with PVA (1800 and 98 000 Da). Higher Mw exhibits fine grains and uniform layers with the t of ∼13 μm in 2 h deposition time due to the greater ion diffusion coefficient, D (1.52 × 10-5 cm2s-1). The post-deposition annealing on the CoSb3 thick film of higher Mw PVA assisted revealed significant enhancement of the S and power factor, PF by over 100% as compared to the as-deposited film. Low electrical conductivity, σ of 7.53 kSm-1 contributes to the high S and PF (annealed at 373.15 K) of 222.75 μVK-1 and 558.17 μWm-1K-2, respectively. This work demonstrates that post-deposition annealing has a prominent effect on thermoelectric properties.